50th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2014
DOI: 10.2514/6.2014-3712
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Assessment of the Role of a Conducting Vacuum Chamber in the Hall Effect Thruster Electrical Circuit

Abstract: The role of the electrically conductive vacuum chamber wall in the completion of the discharge circuit of a Hall effect thruster (HET) is experimentally investigated. The AerojetRocketdyne T-140 laboratory-model HET operating at a discharge voltage of 300 V, discharge current of 5.16 A, and anode flow rate of 5.80 mg/s serves as a representative HET test bed. The nominal facility operating pressure during thruster firings is 4.9 × 10 -6 Torr corrected for xenon. Two 0.91 m x 0.91 m square aluminum plates are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…HET test facilities are also almost ubiquitously metallic and, as such, have finite conductivity. Recent work has indicated that chamber conductivity plays a significant role in the HET electrical circuit, and consequently represents a previously unexplored topic of electrical facility effects [18,19]. Specifically, this work has shown that the facility walls collect a significant fraction of the discharge current and, as such, act as an alternate recombination site for plume ions and electrons that have not undergone recombination before reaching the facility walls.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…HET test facilities are also almost ubiquitously metallic and, as such, have finite conductivity. Recent work has indicated that chamber conductivity plays a significant role in the HET electrical circuit, and consequently represents a previously unexplored topic of electrical facility effects [18,19]. Specifically, this work has shown that the facility walls collect a significant fraction of the discharge current and, as such, act as an alternate recombination site for plume ions and electrons that have not undergone recombination before reaching the facility walls.…”
mentioning
confidence: 90%
“…The magnetic circuit configuration of the T-140 HET (two concentric coils centered on the thruster centerline) restricts the position of the magnetic field separatrix to the thruster centerline and precludes the T-140 HET from exhibiting the off-centerline separatrix surfaces shown in HETs with magnetic coils centered off axis [18][19][20][21]33]. This magnetic field topology eliminates any concerns about the changing nature of the near-field plume properties and cathode coupling as a function of cathode position relative to the absent off-centerline separatrix surface [20].…”
Section: B T-140 Hetmentioning
confidence: 99%
See 1 more Smart Citation
“…A low-density plasma flow (i.e., the HET plume) is then exhausted from the thruster in the axial direction toward the downstream end of the facility. Although some of the emitted ions and electrons recombine before striking the downstream facility surfaces, the ion-electron recombination mean free path is generally longer than the characteristic axial facility dimensions; thus, most of these charged particles strike the downstream facility surfaces, recombine, and reflect as neutrals with a thermal speed characterized by the chamber wall temperature [22,25,28]. Upon reflection, these neutrals are then able to traverse the vacuum facility until they strike and are condensed on one of the cryopumps.…”
Section: A Overview Of Het Vacuum Test Facilitiesmentioning
confidence: 99%
“…Figure 1a shows a schematic of a typical vacuum test facility used for HET testing. These test facilities are usually stainless-steel cylindrical vacuum chambers measuring 4 m or more in length and 2 m or more in diameter, equipped with cryopumps in order to achieve and maintain operating pressures on the order of 10 −5 Torr or less [6,22,[25][26][27]. The cryopumps operate by cooling a plate or series of plates to an operating temperature of approximately 15 K using gaseous helium [22].…”
mentioning
confidence: 99%